Anti-metastasis effect of fucoidan from Undaria pinnatifida sporophylls in mouse hepatocarcinoma Hca-F cells. - Peisheng Wang; Zhichao Liu; Xianli Liu; Hongming Teng; Cuili Zhang; Lin Hou; Xiangyang Zou (PLoS ONE, 2014)
Metastasis is one of the major causes of cancer-related death. It is a complex biological process involving multiple genes, steps, and phases. It is also closely connected to many biological activities of cancer cells, such as growth, invasion, adhesion, hematogenous metastasis, and lymphatic metastasis. Fucoidan derived from Undaria pinnatifida sporophylls (Ups-fucoidan) is a sulfated polysaccharide with more biological activities than other fucoidans. However, there is no information on the effects of Ups-fucoidan on tumor invasion and metastasis. We used the mouse hepatocarcinoma Hca-F cell line, which has high invasive and lymphatic metastasis potential in vitro and in vivo, to examine the effect of Ups-fucoidan on cancer cell invasion and metastasis. Ups-fucoidan exerted a concentration- and time-dependent inhibitory effect on tumor metastasis in vivo and inhibited Hca-F cell growth, migration, invasion, and adhesion capabilities in vitro. Ups-fucoidan inhibited growth and metastasis by downregulating vascular endothelial growth factor (VEGF) C/VEGF receptor 3, hepatocyte growth factor/c-MET, cyclin D1, cyclin-dependent kinase 4, phosphorylated (p) phosphoinositide 3-kinase, p-Akt, p-extracellular signal regulated kinase (ERK) 1/2, and nuclear transcription factor-κB (NF-κB), and suppressed adhesion and invasion by downregulating L-Selectin, and upregulating protein levels of tissue inhibitor of metalloproteinases (TIMPs). The results suggest that Ups-fucoidan suppresses Hca-F cell growth, adhesion, invasion, and metastasis capabilities and that these functions are mediated through the mechanism involving inactivation of the NF-κB pathway mediated by PI3K/Akt and ERK signaling pathways.